Artemisinin and Its Derivatives as a Repurposing Anticancer Agent: What Else Do We Need to Do? - Zhe Li; Qin Li; Jun Wu; Manyuan Wang; Junxian Yu (Molecules, 2016)
Preclinical investigation and clinical experience have provided evidence on the potential anticancer effect of artemisinin and its derivatives (ARTs) in the recent two decades. The major mechanisms of action of ARTs may be due to toxic-free radicals generated by an endoperoxide moiety, cell cycle arrest, induction of apoptosis, and inhibition of tumor angiogenesis. It is very promising that ARTs are expected to be a new class of antitumor drugs of wide spectrum due to their detailed information regarding efficacy and safety. For developing repurposed drugs, many other characteristics of ARTs should be studied, including through further investigations on possible new pathways of anticancer effects, exploration on efficient and specific drug delivery systems-especially crossing biological barriers, and obtaining sufficient data in clinical trials. The aim of this review is to highlight these achievements and propose the potential strategies to develop ARTs as a new class of cancer therapeutic agents.